Pengaruh Implementasi Sistem Informasi Keuangan Desa (SISKEUDES), Kompetensi Aparatur Desa, dan Partisipasi Masyarakat terhadap Akuntabilitas Pengelolaan Keuangan Desa di Kecamatan Nogosari - Rizka Fadhilah Amaliah; Desy Nur Pratiwi; Sri Laksmi Pardanawati (Lembaga Yasin AlSys, 2026)
Problems in village financial management, such as delayed reporting, recording errors, and low transparency, can affect the accountability of village financial management. This study aims to analyze the influence of the implementation of the Village Financial Information System (SISKEUDES), village apparatus competence, and community participation on the accountability of village financial management in Nogosari Subdistrict. This study used a quantitative approach with purposive sampling, involving 65 respondents who were village officials. Data were collected through questionnaire distribution and analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, the F-test, and the t-test with the assistance of SPSS. The results show that the implementation of SISKEUDES, village apparatus competence, and community participation influence the accountability of village financial management. This finding confirms that optimal system implementation, adequate apparatus competence, and active community participation can improve accountability in village financial management. This study contributes to the development of public sector accountability studies, particularly in the context of village financial governance. The practical implications of this study indicate that improving the quality of village financial management can be achieved through optimizing SISKEUDES, strengthening village apparatus competence, and increasing community involvement in village financial oversight.